2019
DOI: 10.1016/j.jvscit.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of fusion imaging in endovascular treatment of occlusive peripheral artery disease

Abstract: Endovascular treatment of peripheral artery disease has dramatically improved in the past decades; however, occlusive or stenotic lesions of the femoral-popliteal artery segment remain a significant challenge for vascular specialists. Real-time guidance based on vessel visualization might be helpful for successful recanalization. Herein, we present three successful cases of fusion imaging during endovascular treatment of the femoral-popliteal artery segments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Preliminary studies on fusion imaging for lower extremities revascularization was reported in several studies for iliac lesions. [10][11][12] At the moment, fusion imaging is not used routinely for the treatment of femoro-popliteal lesions. Moreover, this technology was described only in hybrid rooms equipped with fixed plane sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies on fusion imaging for lower extremities revascularization was reported in several studies for iliac lesions. [10][11][12] At the moment, fusion imaging is not used routinely for the treatment of femoro-popliteal lesions. Moreover, this technology was described only in hybrid rooms equipped with fixed plane sensors.…”
Section: Introductionmentioning
confidence: 99%